Implementing the golden rule for public investment in Europe: Safeguarding public investment and supporting the recovery - Achim Truger (WWWforEurope, 2015)
Most parts of the Euro area have seen seven years of deep economic crisis. The strategy of tightening the fiscal constraints of the SGP has driven many member states into austerity. In contrast, the golden rule of public investment proposed in this study would be one important element of the necessary institutional reform. The rule is widely accepted in traditional public finance and would allow financing net public investment by government deficits thus promoting intergenerational fairness as well as economic growth. A pragmatic version focusing on net public investment as defined in the national accounts minus military expenditures plus investment grants for the private sector could quickly be implemented. Net public investment should be deducted from the relevant deficit measures of the Stability and Growth Pact and the fiscal compact. Over time it could be technically and statistically refined and potentially include other - more intangible - types of investment like education expenditures. As political implementation would probably take some time, the golden rule would have to be complemented by expansionary fiscal policy to provide the urgently needed boost to the European economy in the short term. This could be done by a short term European Investment Programme similar to the 2008 European Economic Recovery Programme during the Great Recession. Such a programme could also allow for investment needs beyond the narrow national accounts definition to contribute to public investment in a broader sense, e.g. for expenditure related to the currently neglected Europe 2020 goals such as social inclusion.
Keywords: E61; E62; E65; H54; H62; 330; Public Investment; Golden Rule; Reform of the Stability and Growth Pact; Fiscal Policy and Macroeconomic Performance; Austerity